THE EFFECTIVENESS PROBLEM BASED LEARNING MODEL OF MATHEMATICS LEARNING REVIEWED BY SELF REGULATED AND ACHIEVEMENT STUDENT FOR 10th GRADE VOCATIONAL HIGH SCHOOL 1 SAPTOSARI - Musyafa Suhadi; Mathilda Susanti (Jurnal Pedagogi Matematika, 2016)
The aim of this study was to know the effectiviteness of problem based learning model in mathematicslearning reviewed by self regulated and achievement student for grade X Vocational High School 1 Saptosari. Thekind of study was a quasi experiment, with an experiment group and a control group. The data were collectedthrough questionnaire of self regulated and test of achievement. The statistic tests were one-sample t test and twosamples t test used software Minitab 16. The results of the study at the significance level of 0,05,it could be inferredthat (1) problem based learning model in mathematics learning effective reviewed by self regulated andachievement student 10th grade in Vocational High School 1 Saptosari (2) problem based learning is more effectivethan ekspositori model in mathematics learning reviewed by self regulated and achievement student 10th grade inVocational High School 1 Saptosari.